2015
DOI: 10.1002/2015gc005858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maghemization on the magnetic properties of nonstoichiometric pseudo‐single‐domain magnetite particles

Abstract: The effect of maghemization on the magnetic properties of magnetite (Fe 3 O 4 ) grains in the pseudo-single-domain (PSD) size range is investigated as a function of annealing temperature. X-ray diffraction and transmission electron microscopy confirm the precursor grains as Fe 3 O 4 ranging from $150 to $250 nm in diameter, whilst M€ ossbauer spectrometry suggests the grains are initially near-stoichiometric. The Fe 3 O 4 grains are heated to increasing reaction temperatures of 120-2208C to investigate their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…(2014) and Almeida et al. (2015). Note that the interaction effects have been considered both in the weighted multilayer and 2‐layer models.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…(2014) and Almeida et al. (2015). Note that the interaction effects have been considered both in the weighted multilayer and 2‐layer models.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, the M rs /M s as a function of oxidation parameter is almost indistinguishable from the experiment results. Another group of systematic experimental data is from Almeida et al (2015), with grains size ranging from ∼150-250 nm. The variation of hysteresis parameters versus oxidation is not as evident as those for finer grains , resembling the modeling results for larger grains with an ESV state (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The SD critical grain size of maghemite is ~60 nm and it is ~50-84 nm for magnetite, 32 although these values can depend on particle shape. 33 Almeida et al 34 have observed almost identical FORC behavior for magnetite and maghemite with similar particle size. Therefore, their similar behaviors makes it difficult to exclusively assign the low-H C component to one of these phases.…”
Section: Micro Samplementioning
confidence: 98%